Advancing energy efficiency: thermomechanical characterization of plastic-infused concrete for sustainable building solutions - Siddique, Mohammed Javeed; Akhas, Punitha Kumar (Comptes Rendus. Chimie)
Global energy demands within buildings are escalating, driven by increased dependence on energy-intensive systems such as air conditioning. This surge necessitates innovative solutions to reduce energy consumption and promote sustainability in construction practices. Simultaneously, the persistent problem of plastic waste presents an environmental challenge, with recycling efforts lagging behind the rapidly growing volumes of discarded materials. This study addresses both issues by investigating the feasibility of using recycled plastic materials—low-density polyethylene (LDPE), polypropylene (PP), polyester, and high-density polyethylene (HDPE)—as partial sand substitutes in concrete for roofing applications. The objectives of this research include reducing air conditioning costs, decreasing carbon emissions, and shortening the payback period for energy-efficient building practices. Specifically, buildings situated in the hot–dry climate of Muscat, Oman, and the composite climate of New Delhi, India, were studied. The evaluation of the modified concrete’s mechanical and thermophysical properties indicates that the incorporation of 30 wt% LDPE yields the most significant economic and environmental benefits. This modification leads to the highest annual savings, calculated at 0.9946 $/m2 in Muscat and 0.9928 $/m2 in New Delhi, along with a marked reduction in carbon emissions—19 kg/kWh in Oman and 18.2 kg/kWh in New Delhi. Additionally, the use of 10 wt% HDPE results in the fastest payback, recorded at 1.37 years.